ANALYSIS OF CONTEXTUAL LEARNING APPLICATION IN THE DEVELOPING OF SHORT STORYTELLING WRITING ABILITY - Mahpudoh Mahpudoh; Diana Romdhoningsih (International Journal of Economy, Education and Entrepreneurship, 2022)
Writing short stories is a skill that can help students become more creative and qualified to generate ideas, thoughts, and ideas, as indicated by using effective sentences and appropriate and precise language. This study is the goal of teaching students to write short tales. Students need to understand better how to create short stories if they learn how to write them. This study aims to (1) present pictures and explanations of instructors who apply the contextual approach in short story learning and (2) to identify the characteristics that determine the effectiveness of teachers who apply contextual approaches, particularly in the setting of short story learning. This study contextualizes short story learning for a single Indonesian language instructor at the ninth-grade level at SMP PGRI Cirus in Serang Regency, Banten. The data is gathered through careful observation, in-depth interviews, and meticulous analysis. In addition, qualitative descriptions were used to assess data collected from three different approaches. This study's findings suggest that (1) teachers who understand the stages involved in implementing the contextual approach to short story learning are more likely to have students who reach the KKM they set for themselves. And (2) students who reach the KKM more often have a more positive experience learning the stories. Teaching variables, student characteristics, facilities and infrastructure, and environmental elements impact teachers' ability to implement a contextual approach to learning short stories successfully